Navigating Conservation Access: Unraveling Ignorant Tourist Behavior and Typologies in Komodo National Park - Rahmafitria, Fitri; Purboyo Hidayat Putro, Heru; Rosyidie, Arief; Dirgahayani, Puspita; Puspito Dyah Setiyorini, Heri; Rohmah Nurazizah, Ghoitsa (Jurnal Manajemen Hutan Tropika, 2024)
The impact of access policies on the influx of ignorant behavior in conservation areas is still understudied. This research aims to detect this ignorant tourist behavior in the conservation areas by analyzing perceived accessibility and examining the tourist typologies. The study was conducted in Komodo National Park, one of the most popular destinations in Indonesia, which has experienced high accessibility development. The research method employed tourism policy and factor-cluster analysis to examine the tourist typology. Accessibility constructs and hedonic tourist motivation were used as the variables in the analysis. The total respondents were 534, and the data were analyzed using a non-hierarchical K-means cluster analysis. The result showed that three aspects were considered in managing the accessibility in the conservation areas. The aspects included destination, individual, and conservation accessibilities in the national park. Further, four tourist typologies were found in this research. Two new typologies, hedonistic adventure tourists and high-risk hedonistic tourists, indicated ignorant behavior. Two others, such as real ecotourists and nature-relaxing tourists, presented general nature-based tourist characteristics in the existing literature. The managerial implications of this research are providing practical insights for planners and destination managers to improve conservation awareness for remarkably ignorant tourists.